“Such a Good Night”: Analyses of Korean-English code-switching and music video comments of ASTRO’S songs - Alya Ditha Berliana; Harwintha Yuhria Anjarningsih (Universitas Pendidikan Indonesia, 2022)
To attract global multilingual audiences, English lyrics had been included in K-Pop songs for decades as a strategy (Lauren, 2018; Sea, 2018). This paper analyzed the English usage of “All Night”, “Blue Flame”, and “Knock” by ASTRO, a third-generation K-Pop group from a non-mainstream agency to examine code-switching and the global recognition of K-Pop songs. All songs were examined by using code-switching theories from Poplack (1980) and Bullock and Toribio (2009) and other theories on function analysis by Lawrence (2010) and Lee (2004) and comment analysis by Fernandez-Martinez et al. (2014) and Kwon (2019). The findings revealed that the majority of code switches in “All Night” and “Blue Flame” were inter-sentential, yet “All Night” and “Knock” were more similar in utilizing English by having a new function (i.e., emphasizing a dialog from one’s perspective), an important addition to Lee’s (2004) functions. Furthermore, from the usage and function analysis and the comment analysis, the audience responses seemed to be influenced by the singers’ mispronunciations and the non-existence of a new function that failed to create uniqueness in English usage in “Blue Flame,” which may have led to the song’s failure to win awards. In conclusion, the research suggested that, in the near-absence of promotional support from the agency, the interplay among the number of switches, accurate pronunciations, and a new English-switching function seemed to play an important role in making “All Night” and “Knock” popular among multilingual audiences.